Primary Retroperitoneal Seminoma Staging and Surveillance by Means of Fluoro-2-Deoxyglucose-Positron Emission Tomography/Computed Tomography - Tianye Liu; Carina Aparici (World Journal of Nuclear Medicine)
Primary retroperitoneal seminoma is a very rare entity. We present a case of 39-year-old male with primary retroperitoneal seminoma with staging and surveillance by means of F-18 fluoro-2-deoxyglucose-positron emission tomography/computed tomography (FDG-PET/CT). The case demonstrates that primary retroperitoneal seminoma can be easy to identify with FDG-PET/CT and potential follow-up on recurrence, or metastatic disease can be performed using this technique.